(untitled) (BIRDEM Medical Journal, 2017)
Background: Diabetic ketoacidosis (DKA) is a medical emergency. DKA may be complicated by acute kidney injury (AKI) and may require renal replacement therapy. Early detection and treatment including treatment of underlying cause and complication(s), if present, is important in determining outcome of DKA. This study was designed to evaluate the incidence of AKI among patients with DKA. Methods: This cross-sectional study was done in BIRDEM General Hospital, Dhaka, Bangladesh from 2008 to 2011. AKI was diagnosed by using acute kidney injury network (AKIN) criteria. Results: Total patients were 200 with slight female predominance (56%). Mean age of the study subjects was 37.6±7.5 years. Incidence of DKA was more in known diabetic patients (71%), more among rural population (53%) and low income group (76.5%). Infection (40.5%) was the commonest precipitating cause followed by non-adherence to insulin therapy (31%). Acute pancreatitis (5%), myocardial infarction (2%), stroke (1%) and surgery (1.5%) were less common causes and aetiology could not be identified in 14% cases. Fifty nine (29.5%) cases were complicated by AKI and among them three (5%) patients required haemodialysis. AKI was more in severe DKA (pH <7) cases and when precipitated by acute pancreatitis and infections. In spite of standard management overall mortality was 6.5%. Conclusion: Almost one-third of DKA cases had AKI in this study, more in DKA cases precipitated by acute pancreatitis and sepsis. Fluid resuscitation resolved AKI in most cases but few cases required renal replacement therapy. Birdem Med J 2018; 8(1): 26-29